Anisotropic stiffness gradient-regulated mechanical guidance drives directional migration of cancer cells. (1st April 2020) - Zhang, Haihui; Lin, Feng; Huang, Jianyong; Xiong, Chunyang
Abstract: Interfacial interactions between cancer cells and surrounding microenvironment involve complex mechanotransduction mechanisms that are directly associated with tumor invasion and metastasis. Matrix remodeling triggers heterogeneity of stiffness in tumor microenvironment and thus generates anisotropic stiffness gradient (ASG). The migration of cancer cells mediated by ASG, however, still remains elusive. Based on a multi-layer polymerization method of microstructured hydrogels with surface topology, we develop an in vitro experimental platform for mechanical interactions of cancer cells with ASG matrix microenvironment. We show that mechanical guidance of mesenchymal cells is essentially modulated by ASG, leading to a spontaneous directional migration along the orientation parallel to the maximum stiffness although there is no stiffness gradient in the direction. The ASG-regulated mechanical guidance presents an alternative way of cancer cell directional migration. Further, our findings indicate that the mechanical guidance occurs only in mesenchymal cancer cells, but not in epithelial cancer cells, implying that cell contractility may contribute to ASG-regulated migration of cells. This work is not only helpful for elucidating the role of matrix remodeling in mediating tumor cell invasion and metastasis, but has potential implications for developing specific cancer treatments. Statement of Significance: Local extracellular matrix (ECM) stiffening triggers mechanical heterogeneity in tumor microenvironment, which can exert a crucial impact on interfacial interactions between tumor cells and surrounding ECM. The underlying mechanobiological mechanism that tumor cells are modulated by mechanically heterogeneous ECM, however, still remains mysterious to a great extent. Through our established in vitro platform and analysis, we have demonstrated that anisotropic stiffness gradient (ASG) has the ability to elicit directional migration of cells, essentially depending on local stiffness gradients and the corresponding absolute stiffness values. This study is not only crucial for revealing the role of matrix remodeling in regulating tumor invasion and metastasis, but also offers a valuable guidance for developing anti-tumor therapies from the biomechanical perspective. Graphic abstract: Image, graphical abstract